Comparative evaluation of different plant residues on the soil and leaf chemical composition, growth, and seed yield of castor bean (Ricinus communis) - E. I., Moyin Jesu (Universiti Putra Malaysia Press, 2004)
This work investigated the effect of plant residues such as cocoahusk, ricebran and saw dust on the growth, seed yield, leaf and soil chemical composition of castor bean in 1999 and 2000 at Akure in the rainforest zone of Nigeria. The treatments were applied at 6t/ha, replicated four times and arranged in a randomized complete block (RCB) with NPK 15 -15 -15 fertilizer applied at 300 kg/ha and a control (no fertilizer; no residue). The soil and organic amendments were chemically analyzed. The parameters recorded for castor oil bean were plant height, leaf area, stem girth, soil and leaf N, P, K, Ca, Mg, Soil pH, O.M and seed yield. Results showed that there were significant increases (p<0.05) in plant height, leaf area index, stem girth, soil and leaf N, P, K, Ca, Mg, soil pH, O.M and seed yield of castor oil plant under different organic amendment treatments compared to the control. The cocoahusk treatments increased seed weight by 55% and 80% in the two crops of castor oil bean to the ricebran treatment. Compared to the plant residues, the NPK treatment resulted in the greatest increases in the plant height, leaf area and stem girth but reduced seed yield.